ANALYSIS OF THE ABILITY OF ACCOUNTING STUDENTS TOWARDS MASTERY OF THE ENGLISH TERMINOLOGY OF ACCOUNTING: A CASE STUDY ON ACCOUNTING STUDENTS ON SEMESTER IV OF FACULTY OF SOSIAL SAINS UNIVERSITY OF PEMBANGUNAN PANCA BUDI - Efrizah, Doni Efrizah (Accounting and Business Journal, 2019)
This research is about an analysis of the ability of Accounting students towards mastery of the English terminology of Accounting: a Case Study On Accounting Students on Semester IV of Faculty of Sosial Sains, University of Pembangunan Panca Budi. Many students feel difficult to understand and to master English for Accounting especially English terms in accounting hence this analysis is very important to do to see the lack of ability of the students in the mastery of the English terminology of Accounting as well as to improve the way to learn for students. The analysis is done using interview to students by answering questionnaire in Google Form. There are 119 respondents and they have different answers. This research used qualitative approach thus the result and discussion are in the form of description.